GAMBARAN KUALITAS PENILAIAN RUMAH SEHAT DIPERMUKIMAN WILAYAH RW 08 MEDOKAN SEMAMPIR SURABAYA - Sulfi Titianto; Merry Sunaryo; Abdul Hakim Zakkiy Fasya; Agus Adriansyah Aan Adriansyah (Universitas Fort De Kock, 2021)
ABSTRACT A healthy house is a house that allows its residents to develop and foster physical, mental and social in the family, therefore the researcher aims to examine the description of the quality of the assessment of a healthy house in the RW 08 Medokan Semampir settlement, Surabaya. The method used in this research is descriptive quantitative to describe and explain a situation that exists in the research location. Based on the results of this study, it shows that those who meet the requirements for the type of wall and layout, do not meet the requirements for the type of roof, type of floor, type of lighting, which meet the requirements of sanitation facilities, types of clean water facilities, do not meet the requirements for facilities, conditions of trash bins, behavior of residents cleaning the house and page, showing qualified results. The components of the house are roof type, ventilation type, sanitation facilities, latrine facilities and waste water disposal facilities. The behavior of the occupants in disposing of the feces of infants and toddlers indicates that they do not meet the requirements. The conclusion in this study is that the results of the healthy home assessment show 7 components, facilities, eligible behavior, 8 components, facilities, and behavior that does not meet the requirements. Suggestions are that education and home inspections are expected to be carried out every three months from further health center sanitation workers. Keywords: Healthy House, Sanitation, Occupant Behavior ABSTRAK Rumah sehat adalah rumah yang memungkinkan bagi penghuninya untuk mengembangkan dan membina fisik mental dan sosial didalam keluarga maka dari itu peneliti bertujuan untuk meneliti gambaran kualitas penilaian rumah sehat di permukiman RW 08 Medokan Semampir Surabaya. Metode yang digunakan dalam penelitian ini kuantitatif deskriptif untuk menggambarkan dan mejelaskan suatu keadaan yang ada di lokasi penelitian. Bedasarkan hasil penelitian ini menujukan yang memenuhi syarat jenis dinding dan tata ruang, tidak memenuhi syarat jenis atap , jenis lantai, jenis pencahayaan, yang memenuhi syarat sarana sanitasi, jenis sarana air bersih, tidak memenuhi syarat sarana kondisi tempat sampah , perilaku penghuni membersikan rumah dan halaman, menujukan hasil memenuhi syarat. Komponen rumah jenis atap, jenis ventilasi, Sarana sanitasi, sarana jamban sarana pembuangan air limbah. Perilaku penghuni membuang tinja bayi dan balita, menujukan tidak memenuhi syarat. Kesimpulan dalam penelitian ini adalah dari hasil penilaian rumah sehat tersebut menujukan 7 komponen, sarana, perilaku memenuhi syarat, 8 komponen, sarana, perilaku tidak memenuhi syarat. saran diharapkan diadakan edukasi dan pengecekan rumah selama tiga bulan sekali dari petugas sanitasi puskesmas lebih lanjut. Kata kunci: Rumah Sehat, Sanitasi, Perilaku Penghuni